Modeling choice behavior of non-mandatory tour locations in California – An experience. (July 2018) - Basu, Debasis; Stefan, Kevin John; Hunt, John Douglas; McCoy, Michael
Highlights: The primary location choice model for non-mandatory tour. It addresses many tour purposes, which were not explicitly addressed in previous works. The model is developed under a reverse hierarchy structure of joint tour location and mode choice. The work identifies new evidences on a list of attractors influencing the choice model. Abstract: The paper presents behavioral model of a primary location choice for home-based non-mandatory tours. The choice model addresses an array of non-mandatory tour purposes. Though some of them are found in literature, such as shopping, recreation and entertainment, many of them such as personal business, social, eat and escort are not explicitly addressed in literature. In this study, the primary location choice model is developed under a certain nesting hierarchy of a joint tour location and mode choice, where tour mode choice is generally found a foregone conclusion upon which location choice is conditioned. The work reveals a list of attractors influencing the primary location choice behavior of an individual for a specific non-mandatory tour purpose. The study highlights the need for more introduction of transit-oriented service across the state of California, which is found a preferred option by individuals for non-mandatory tours such as shopping, recreation or entertainment, social etc. The study is demonstrated using household travel diary data for California, which is revealed preference in nature.